STRATEGI PENDIDIKAN BERKARAKTER DI ERA DIGITAL SEKOLAH ISLAM TERPADU CIBINONG - Syukrillah, Muhammad Yazid; Pranitasari, Diah (Universitas Ichsan Sidenreng Rappang, 2025)
This study aims to formulate a strategy for Character Education in the digital era of Islamic Schools. Using a descriptive and exploratory approach, this study combines qualitative and quantitative methods with SWOT and AHP analysis. Data were collected through purposive sampling involving principals, senior teachers, management staff, and parent representatives. The results of the PESTEL analysis show that political, economic, social, technological, environmental, and legal factors provide opportunities and challenges for SIT. Industry analysis using Porter's Five Forces reveals a high level of competition, with threats from new entrants and substitute products. Through the SWOT matrix, internal strengths and weaknesses as well as external opportunities and threats faced by the school were identified. The proposed strategies include developing superior character and technology-based programs, digitizing the academic system, improving the quality of human resources, and strengthening partnerships with Islamic institutions. The AHP method was used to set strategic priorities, with the results showing that learning and curriculum innovation strategies are the main priorities. This study provides concrete recommendations to improve the competitiveness and quality of education at SIT Al-Fath, as well as building a reputation as a leading Islamic school in the Cibinong area.